Comparative analysis of crab growth performance, enzyme activity, and microbiota between rice-crab coculture and pond farming systems - Zhu, Xiaochen; Nie, Miao; Sun, Na; Zhang, Yazhao; Sun, Mingxia; Li, Changlei; Jiang, Qing; Wei, Hua; Li, Yingdong; Hu, Qingbiao; Zhao, Yingying; Li, Xiaodong (Frontiers in Veterinary Science, 2025)
IntroductionTo support the sustainable development of rice and aquaculture industries, various rice-animal coculture systems have been developed. One such system, the rice-crab coculture system (RCC), has been practiced for decades in northern China. However, studies on the crab physiological status in RCC remain limited. Microorganisms play a crucial role in aquaculture by influencing animal nutrition, health, nutrient cycling, water quality, and environmental impact. Research on the gut and environmental microbiota in RCC is scarce.MethodsThis study compared the growth performance, immune and digestive enzyme activities of crabs between RCC and traditional pond farming system (PF). In addition, the microbiota in crab guts, water, and sediment from both systems was investigated using 16S rRNA gene sequencing.ResultsCrabs in RCC exhibited superior growth performance and higher enzymatic activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), lipase (LPS), and trypsin (TRY). Significant differences were observed in microbiota composition across crab gut, water, and sediment samples, respectively. RCC crabs had a lower abundance of Bacteroidota and a higher abundance of Firmicutes in their gut microbiota. The RCC environment was enriched with beneficial bacteria such as Rhizobiales, Methylococcales, KD4-96, C39, Xanthomonadales, and Nitrosomonadaceae. Microbial function predictions confirmed enhanced methanotrophy and nitrogen fixation in the RCC.DiscussionThe RCC enhances the growth rate and immune capability of crabs. Crabs from RCC consume more animal-based nutrition, which results in distinct differences in gut microbiota composition and higher levels of LPS and TRY compared to those in PF. Additionally, RCC supports environmentally beneficial bacteria that contribute to greenhouse gas reduction, carbon and nitrogen fixation, organic matter decomposition, and ammonia oxidation, benefiting both the crabs and their ecosystem. These findings enhance our understanding of crab physiology and microbial communities in RCC and PF systems.